CUET-PG - Geography entrance exam (NTA) : common university enterence test for PG students - Ajhar Hussain; R. Gupta's Popular Master Guide; Exam pattern (New Delhi : Ramesh Publishing House, 2025)
CUET-PG: MA/M.Sc GEOGRAPHY Entrance Exam Guide" by Ajhar Hussain, published by Ramesh Publishing House, is an excellent resource for students preparing for the CUET Geography exam for postgraduate courses. The book is well-structured and designed to align with the latest syllabus, offering specialized study material that covers all essential topics clearly and comprehensively. It includes solved previous years' papers, which help familiarize students with the exam pattern and question types. The practice questions are meticulously modeled on past exam papers, providing valuable practice and helping to reinforce key concepts. The book is structured to facilitate self-study and revision, making it an indispensable tool for last-minute preparation. Additionally, its focus on the current exam pattern ensures that students stay updated with the latest trends in the exam format. The content is presented in a simple and lucid manner, making complex geographical concepts more accessible. This guide is particularly useful for those aiming for a seat in a prestigious PG program, as it not only prepares students for the exam but also builds confidence. Overall, the book is an excellent choice for self-study and for those looking to excel in the CUET Geography entrance exam.
Keywords: CUET-PG Geography syllabus; Practice questions; Previous years' papers; Clear explanations